Diagnostic Value of High-Resolution Ultrasound for the Evaluation of Capsular Width in Temporomandibular Joint Effusion - Daniel Talmaceanu; Lavinia Manuela Lenghel; Csaba Csutak; Nicolae Bolog; Daniel-Corneliu Leucuta; Horatiu Rotar; Ioan Tig; Smaranda Buduru (Life, 2022)
Aim: The aim of this study was to evaluate if the increased temporomandibular joint (TMJ) capsular thickness, measured by ultrasound (US), is associated with the presence of effusion, diagnosed using MRI imaging. Materials and Methods: 102 patients with signs and symptoms of temporomandibular disorders were included in the study. Each patient underwent US and MRI examinations, 1 to 5 days following clinical examination. The US was performed with an 8–40 MHz linear transducer operating at 20 MHz. The MRI was performed using a 1.5 T MRI device. The ROC curve was analyzed to identify the optimal cut-off value for capsular distention, which can be interpreted as an indirect sign of TMJ effusion. Results: The capsular width values were found to be between 0.7 and 3.6 mm. The best cut-off value was 2.05 mm with a sensitivity of 55.9% and a specificity of 94.7%. The next optimal cut-off value was 1.75 mm with a sensitivity of 67.6% and a specificity of 82.4%. The area under the ROC curve was 0.78 (95% CI 0.68, 0.87, p < 0.05). Conclusions: Ultrasound-measured capsular width can be interpreted as an indirect sign of TMJ effusion. The critical cut-off for capsular width was 2 mm.